Comparison of minimal-flow sevoflurane versus desflurane anesthesia: randomized clinical trial - Berna Ayanoğlu Taş; Ceren Şanlı Karip; Süheyla Abitağaoğlu; Mehmet Celal Öztürk; Dilek Erdoğan Arı (Brazilian Journal of Anesthesiology, 2022)
Background and objectives: Minimal-flow anesthesia provides various advantages, such as reduced environmental pollution, proper humidification and warming of anesthetic gases, and reduced costs. The aim of this study was to compare the cost-effectiveness of minimal-flow sevoflurane and desflurane anesthesia and their effects on hemodynamics, postoperative recovery, respiratory parameters, and liver and kidney functions. Methods: A total of 60 ASA I–II patients aged 18–70 years who underwent posterior spinal instrumentation were included in the study. The patients were divided into Group S (sevoflurane) and Group D (desflurane). After anesthesia induction, the gas flow was initiated at a rate of 4 L.min-1 using a concentration of 8% in Group D and 3.5% in Group S, and the time to reach 0.8 MAC was recorded. The gas flow was then switched to minimal flow. Patient hemodynamic and respiratory parameters, body temperatures and arterial blood gas levels were recorded. The integrated pulmonary index (IPI) was monitored postoperatively. Biochemical findings were recorded 12 hours after the operation. The amount of bleeding and blood transfused, and the costs involved were calculated. Results: The patients’ demographic characteristics, duration of surgery, hemodynamic parameters, IPI values, body temperatures, and arterial blood gas levels were similar at all time points. Biochemical findings, amount of bleeding and amount of blood transfused were similar between the two groups. The mean cost was lower in Group S than in Group D (p = 0.007). Conclusion: The study found no significant difference in terms of reliability between minimal-flow sevoflurane and desflurane anesthesia. Furthermore, the procedure was found to be more cost-effective for Group S than for Group D.